Review of host-directed immunotherapy and candidate agents against leishmaniasis - Tamir, Mebratu; Birke Teketelew, Bisrat; Berta, Dereje Mengesha; Angelo, Abiy Ayele; Terekegne, Amare Mekuanint; Cherie, Negesse; Mekonnen, Gebeyaw Getnet; Abere, Aberham; Eshetu, Tegegne (Frontiers in Tropical Diseases, 2025)
Leishmaniasis are a group of neglected tropical vector-borne diseases caused by an obligate intracellular protozoan parasite of the genus Leishmania. Currently, standard chemotherapy has challenges due to its cytotoxicity, cost, painful route of administration, long treatment duration, resultant partial efficacy, and high risk of resistance. To overcome this issue, new intervention approaches have been formulated to treat leishmaniasis. Host-directed immunotherapy is a novel approach that involves the adoptive transfer of host-derived biomolecules to enhance the natural power of protective cellular immunity. This restores the function of effector cells, enabling them to clear intracellular amastigotes and leads to the recovery of patients from infections. The advantages of this modality over routine treatment include less cytotoxicity, short hospitalization, affordability, and better efficacy for drug-resistant parasite strains. Several studies have reported better efficacy of this treatment model for drug-resistant Leishmania species. However, current knowledge and evidence are highly insufficient to implement this agent to treat any form of leishmaniasis. This review aims to show the efficacy of this immunotherapeutic agent against leishmaniasis. The discussion has focused on major pro-inflammatory cytokines (interferon-gamma, interleukin-12, and granulocyte-macrophage colony-stimulating factors), immune cells (dendritic and mesenchymal stem cells), and monoclonal-antibodies (anti-interleukin-10, anti-interleukin-4, and immune checkpoint inhibitory molecules). Our finding shows that this treatment approach has the potential to be a successful treatment and improve clinical outcomes by reducing the adverse effects of routine therapy. This suggests the future deployment of this treatment modality as an alternative strategy. However, it needs extensive pre-clinical trials using local animal models that reflect typical host immunological profiles against leishmaniasis in order to select the most protective candidate agents.